Developing Career Counseling Applications on Guidance and Counseling Study Program Universitas Negeri Medan - Asiah, Asiah; Ginting, Rafael Lisinus; Sari, Armita; Violina, Erwita Ika (International Journal of Applied Counseling and Social Sciences, 2024)
The presence of computers and information technology has brought many changes to human life, including the field of career counseling. The aim of this research is to develop a website-based career counseling application. The development model used is 4D, which includes the definition, design, development and dissemination. This research was conducted at Universitas Negeri Medan which began with collecting initial data related to data on career exploration problems, career selection and lifelong career development. The data collection techniques for this research are interviews, observations and questionnaires for material experts and information technology experts. As a result, the process of developing a career application based on the GCC-Learning.com website has components that suit the needs of Medan State University students. It is known that the need for information and career assistance has been met, but has not resulted in positive changes as expected, because the application being developed is still relatively new and has not been well socialized among students. It is hoped that the results of this research will be useful for all parties involved in student career development issues.